Ultra-compact MXene fibers by continuous and controllable synergy of interfacial interactions and thermal drawing-induced stresses - Zhou, Tianzhu; Yu, Yangzhe; He, Bing; Wang, Zhe; Xiong, Ting; Wang, Zhixun; Liu, Yanting; Xin, Jiwu; Qi, Miao; Zhang, Haozhe; Zhou, Xuhui; Gao, Liheng; et al. (Nature communications, 2022)
Recent advances in MXene (Ti 3 C 2 T x ) fibers, prepared from electrically conductive and mechanically strong MXene nanosheets, address the increasing demand of emerging yet promising electrode materials for the development of textile-based devices and beyond. However, to reveal the full potential of MXene fibers, reaching a balance between electrical conductivity and mechanical property is still the fundamental challenge, mainly due to the difficulties to further compact the loose MXene nanosheets. In this work, we demonstrate a continuous and controllable route to fabricate ultra-compact MXene fibers with an in-situ generated protective layer via the synergy of interfacial interactions and thermal drawing-induced stresses. The resulting ultra-compact MXene fibers with high orientation and low porosity exhibit not only excellent tensile strength and ultra-high toughness, but also high electrical conductivity. Then, we construct meter-scale MXene textiles using these ultra-compact fibers to achieve high-performance electromagnetic interference shielding and personal thermal management, accompanied by the high mechanical durability and stability even after multiple washing cycles. The demonstrated generic strategy can be applied to a broad range of nanostructured materials to construct functional fibers for large-scale applications in both space and daily lives. Forming compact layered nanostructures is key to achieving continuous MXene fibers with electrical and mechanical properties. Here, authors demonstrate ultra-compact high-performance MXene fibers via a controllable synergy of interfacial interactions and thermal drawing-induced stresses.